Hubungan Efikasi Diri Dan Kecemasan Dengan Motivasi Belajar Pada Mahasiswa (ILIN Institute, 2020)
Purpose: to determine the relationship of self-efficacy and anxiety with learning motivation. Methodology: quantitative type with analytic design and cross sectional approach. Results: respondents in this study were 123 respondents, the distribution of the highest learning motivation variables with moderate learning motivation levels (69,9%), while for the highest self-efficacy variables with high self-efficacy levels (97.6%) and for variables anxiety is highest with moderate anxiety level (57,7%). The results of correlation analysis on learning motivation variables with self-efficacy obtained P 0,000 and the results of the correlation coefficient r 0.527. While the results of correlation analysis on variables Motivation learning with Anxiety obtained P  0.025 and the results of the correlation coefficient r -0.203. Conclusion: there is a relationship between self-efficacy and anxiety with learning motivation.